????? ?????? ????????? ??? ?????? - Mufilhah Mufilhah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2016)
Sociolinguistics is the branch of linguistics that examines the relationship between language and the speakers. This study specifically discusses the contextual study of the variations in the use of language communities that are affected by differences in the sociocultural aspects of society. Sociolinguistics also discusses the relationship between language and society, the use of language and social structure of the language. The social life of a complex society there are various variations of the language. Language variations provide a wealth of information about how the language is used, the social relations in a community language, and other aspects of social identity through the language they use. The use of language variation or a variety of diverse languages is a richness that is very unusual, because the study sociolinguistics never saw that kind of language contained in the community is something that is wrong or right, but only sociolinguistics examines the emergence of language diversity. The term sociolinguistic basically already used by scholars qudama 'in the books turast especially Imam Jahidz in the book hayawan bayan wa tabyin and other books, which discusses issues relating to regional variations of someone with his social status in the community as well as groups a different profession or position in society tend to use a variety of different languages